Self-Efficacy, Computer Anxiety, Trait Anxiety, and Cognitive Distortions Influence Students' Interest in Learning Mind Your Own Business - Sibarani, Blasius Erik (Jurnal Pendidikan, 2024)
The purpose of this study was to determine the effect of self-efficacy, computer anxiety, trait anxiety, and cognitive distortions on students' interest in learning Mind Your Own Business (MYOB). This research is a quantitative study using raw data obtained from questionnaires and data analysis. This study used multiple linear regression and data collection techniques in the form of questionnaires. The data obtained were analyzed by f-test, t-test, and multiple linear regression analysis. The results showed that partially the self-efficacy variable affected students' interest in learning MYOB, computer anxiety influenced students' interest in learning MYOB, trait anxiety had an impact on students' interest in learning MYOB, and cognitive distortions affected students' interest in learning MYOB. The practical implication of this research is that it is essential to ensure that students have good self-efficacy, low anxiety levels, and no cognitive deviations.